Neuromodulação cerebral no transtorno do espectro autista - Bezerra, Anuska Erika Pereira (2022)
Autistic Spectrum Disorder is a group of neurological development disorders with early onset, characterized by impaired social and communication skills, in addition to restricted and stereotyped behaviors. It has been argued that such characteristics are the result of brain anatomophysiological changes, caused by functional abnormalities in specific areas, imbalance in neuronal excitability, decreased cortical plasticity, as well as failures in long-range connections between brain lobes. Due to the central components of symptoms, neuromodulatory techniques have gained prominence, among them Transcranial Direct Current Stimulation - ETCC. The focus of the present study was to identify not only whether ETCC is effective in reducing clinical symptoms, but also whether it was able to modulate the cortical electrical activity of patients with ASD, through the Electroencephalogram - EEG exam. Three articles were developed, the first corresponds to a scope review, the second to a proof-of-concept clinical study and the third was an empirical study of the first results of the clinical trial. The first study was conducted with a scooping review in order to verify the updated state of the art of the application of the main techniques of non-invasive brain stimulation (rTMS, theta-burst stimulation, tdcs, vagal stimulation) in pediatric populations. Based on this assumption, it was thought to combine behavioral measures with an electrophysiological marker and correlate with the therapeutic benefit of ETCC. In this way, the second article corresponds to a proof-of-concept study, whose objective was to expose the procedures that were adopted in the clinical trial, double blind, placebo-controlled that combined the application of ETCC to the examination of Electroencephalography. The third article evaluated in 20 subjects whether the ETCC was able to modulate the presentation of the frequency bands, Theta, Alpha and Beta, in addition to the microrestates of the frequency bands in the experimental group, in relation to the placebo and control, mainly in frontal regions, temporoparietal and limbic disorders, in addition to checking the behavioral components of post-apical behavior. It is concluded that ETCC is promising in the symptomatological treatment of ASD, however more controlled clinical studies are needed to replicate results and ensure the generalization of effects.